KUALITAS PELAYANAN PUBLIK DI KANTOR KECAMATAN MODAYAG KABUPATEN BOLAANG MONGONDOW TIMUR - IDRIS, JHODDY DWIKY; PANGKEY, MASJE; MAMBO, RULLY (JURNAL ADMINISTRASI PUBLIK, 2021)
The provision of services that meet the standards that have been set is indeed a part that needs tobe observed. Currently, it is often felt that even the minimum service quality is still far from people'sexpectations. Likewise with the Modayag sub-district government which is the first spearhead in providingservices to the community. In serving the community, the sub-district government is also inseparable fromproblems related to relatively unsatisfactory service conditions. Various obstacles that exist in the field arethe cause of the ineffectiveness of service delivery at the Modayag District Office, East BolaangMongondow Regency. This study aims to answer questions about quality of public services at theModayag District Office, East Bolaang Mongondow Regency. In this study using the dimensions ofservice quality from Zeithaml. Tangible, Reliability, Responsiveness, Assurance, and Empathy. Qualitymeasurement aims to determine the factors of the quality of public services at the Modayag sub-districtoffice, East Bolaang Mongondow Regency. This study uses qualitative research methods by conductingdata collection methods by interviewing 10 informants in direct observation, looking for documentsrelated to research assisted by recording devices and writing instruments. The results of this study indicatethat service delivery at the Modayag District Office, North Bolaang Mongondow Regency has not beenmaximized.Keyword : Quality, Public Services